Biomechanical issues of abdominal and groin injuries in tennis - Knudson, D. (Medicine and Science in Tennis, 2007)
Many kinds of evidence must be integrated to determine the mechanism of common injuries in sport. One of the most important areas of research comes from biomechanics. Knowledge of the normal motion of the body, the kinetics that create that motion, as well as pathomechanics, allows sports medicine professionals to diagnose and treat sport injuries more accurately. There are many kinds of biomechanics research that provide this indirect evidence about the likely mechanisms of sport injury. This paper will summarise biomechanical loading and some of these lines of evidence that have focused on the biomechanics of the hip and lower trunk motion in tennis. In summary of the results, the typical loads experienced by the hip abductors/adductors in tennis strokes and the lateral movements on court are considerably safe. These results are also consistent with the clinical observations of unusual events related to fatigue, slipping, or some event contributing to an acute injury. More data on this subject is needed, since the predominance of biomechanical research on tennis strokes and movements has not focused on the hip, trunk, and transverse plane variables.